Generative Adversarial Networks applied to Telecom Data - Using GANs to generate synthetic features regarding Wi-Fi signal quality - Espindola, Tatiane Sander (2021)
Project Work presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics